2007
DOI: 10.1016/j.juro.2007.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Followup After Elective Testis Sparing Surgery for Leydig Cell Tumors: A Single Center Experience

Abstract: In patients with Leydig cell tumors testis sparing surgery with frozen section examination provides an excellent long-term oncological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 20 publications
2
65
1
4
Order By: Relevance
“…15 Prior single institution experiences suggest the majority of SCST are benign and rarely progress. 3,16 Conversely, the minority of patients that do present with metastatic disease have a poor prognosis. 7,8,17 In our series, patients with metastatic SCST at presentation have a two-year CSS of 30%, compared to a two-year CSS of 95% in those presenting with stage I disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Prior single institution experiences suggest the majority of SCST are benign and rarely progress. 3,16 Conversely, the minority of patients that do present with metastatic disease have a poor prognosis. 7,8,17 In our series, patients with metastatic SCST at presentation have a two-year CSS of 30%, compared to a two-year CSS of 95% in those presenting with stage I disease.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge is derived from single-institution experiences and small retrospective case series. Individual case reports have suggested that SCSTs exhibit a benign course and rarely recur, indicating that surgical treatment with orchiectomy alone will cure majority of these tumours; [3][4][5][6] however, in a minority of cases, metastatic disease is found at the time of diagnosis. The prognosis for these individuals is poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in most cases, the standard therapy for benign Leydig cell tumors is considered to be orchiectomy. Recently, by retrospectively analyzing the long-term follow-up of a series of patients with Leydig cell tumors electively treated with testis sparing surgery, Glannarin et al (5) demonstrated that testis sparing surgery with frozen section examination has an excellent long-term oncological outcome. Therefore, testis-sparing surgery may be chosen for treating benign Leydig cell tumors to maintain fertility, especially in boys and young men (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by retrospectively analyzing the long-term follow-up of a series of patients with Leydig cell tumors electively treated with testis sparing surgery, Glannarin et al (5) demonstrated that testis sparing surgery with frozen section examination has an excellent long-term oncological outcome. Therefore, testis-sparing surgery may be chosen for treating benign Leydig cell tumors to maintain fertility, especially in boys and young men (5)(6)(7)(8)(9). If the tumor is malignant, orchiectomy with retroperitoneal lymph node dissection is recommended, since chemotherapy and radiation therapy show limited efficacy in the treatment of malignant Leydig cell tumors.…”
Section: Introductionmentioning
confidence: 99%